Outage Analysis of Multi-IRS Wireless Communication over κ-μ Fading with Panel Selection - Hindustani R.K.; Sharma S.; Dixit D. (My University, 2025)
An analysis of the outage probability (OP) has been presented for a wireless communication system that utilizes multiple intelligent reflecting surfaces (IRS) to help in single-input single-output (SISO) transmission. The system also incorporates IRS panel selection diversity and operates over κ-μ fading channels.The message is sent from single transmitting node to single receiving node via best IRS panel to maintain the quality of service (QoS) and enhance the end user experience. The considered system model is very practicable uplink wireless scenario for the next generation wireless communication system. We have developed a precise analytical expression for the OP by considering the presence of numerous IRS elements within each IRS panel. We conduct a comprehensive analysis of the impact of different system characteristics, such as the IRS panel, multipath clusters, and number of reflecting surfaces, on the performance of the OP. Furthermore, we verify the precision of our analytical discoveries by comparing them with simulated outcomes. © 2024 IEEE.